Penyuluhan Pendidikan Seksualitas sebagai Upaya Preventif Kekerasan Seksual Sejak Dini di Sekolah Dasar - Bachrul Ulum; Leny Suryaning Astutik; Dwi Agustina Rahayu; A.A. Putu Eka Putra (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Cases of sexual violence against children in Indonesia continue to rise, with primary school pupils being the most vulnerable group. Cultural stigma, which regards sexuality education as a taboo subject, exacerbates this vulnerability due to limited communication about self-protection within both school and family environments. This community service initiative aims to enhance pupils’ knowledge, awareness and protective skills, whilst equipping teachers with appropriate communication strategies for sexuality education. The activity was held on 16 May 2026 at SDN 1 Beji, Boyolangu Sub-district, Tulungagung Regency, involving around 60 participants comprising pupils and teachers. The programme employed an educational-participatory approach using methods such as interactive lectures, group discussions, case studies, and question-and-answer sessions, supported by edutainment media including animated videos, role-plays, scenario cards, and educational songs. The activity took place in three stages: preparation, implementation, and evaluation. The results of the participant feedback questionnaire showed a very positive response, with an average rating of ‘very good’ above 86% across all assessment aspects. Teachers expressed a strong commitment to building a protective environment for children. This programme is recommended for institutionalisation as a sustainable collaboration between schools and families in efforts to prevent sexual violence against children at an early stage.